Studies on Metal Complexes of Schiff Bases Derived from Sulphadiazine and Sulphadimidine with 5-Substituted Salicylaldehydes - Goel, Sudha; Lal, Keemti (Asian Journal of Chemistry, 2010)
Oxovanadium(IV), iron(III}, cobalt(II), nickel(II) and copper(II) complexes of schiff bases derived from sulphadiazine and sulphadimdine with 5-nitrosalicylaldehyde and 5-chlorosalicylaldehyde have been prepared and characterized by elemental analysis, IR, magnetic moment and electronic spectral data. The schiff bases and their metal complexes have also been subjected to fungicidal screening for studing their antifungal activity.